The use of seed proteins revealed by SDS-PAGE in taxonomy of some Lathyrus L. species grown in Turkey - Emre, Irfan; Turgut-Balik, Dilek; Genc, Hasan; Sahin, Ahmet (My University, 2006)
In this study total 9 taxa belong to four different sections (Pratensis, Orobon, Orobus and Platystylis) collected from different regions of Turkey have been studied for the analysis of seed storage protein profiles to examine their relationship by sodium dodecyl sulphate polyacrilamide gel electrophoresis (SDS-PAGE) technique. Data obtained from electrophoresis of seed proteins were analysed using hierarchical clustering analysis and Euclidean distance was used for calculating the genetic resemblance. Dendogram was formed using average linkage. Electrophoretic protein profiles of seed cotyledons were showed that all taxa except for L. brachypterus var. brachypterus formed two clusters. The first one consisted of L. pratensis, L. laxiflorus subsp. laxiflorus, L. roseus and the second one L. digitatus, L. spathulatus, L. boissieri L. nivalis and L. aureus. In addition, total protein profile differences were observed when four taxa originated from 9 geographical regions belong to three sections (Sections Platystylis, Pratensis and Orobon) were analysed. Protein amount was found to be highest in L. spathulatus and lowest in L. brachypterus var. brachypterus. © 2006 Asian Network for Scientific Information.
Keywords: Cluster analysis; Lathyrus; Seed protein; Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE); Taxonomy; Total protein